1997
DOI: 10.1007/s001250050830
|View full text |Cite
|
Sign up to set email alerts
|

Social inequality in coronary risk: Central obesity and the metabolic syndrome. Evidence from the Whitehall II study

Abstract: SummaryThis report describes the social distribution of central obesity and the metabolic syndrome at the Whitehall II study phase 3 examination, and assesses the contribution of health related behaviours to their distribution. Cross-sectional analyses were conducted utilising data collected in 1991-1993 from 4978 men and 2035 women aged 39-63 years who completed an oral glucose tolerance test. There was an inverse social gradient in prevalence of the metabolic syndrome. The odds ratio (95 % confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
283
1
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(317 citation statements)
references
References 52 publications
26
283
1
7
Order By: Relevance
“…27 Early development during childhood of chronic diseases such as obesity, type 2 diabetes, hypertension and coronary heart disease differs between populations, 28,29 and several studies have shown that SES strongly influences the risk of such diseases. 25,30 Health inequalities are most prominent during childhood, 31 and SES inequalities may influence risk of cardiovascular diseases and health. 32,33 In addition, data published indicate that SES differences in adolescent health influence diet quality and both dietary and physical activity patterns.…”
Section: Introductionmentioning
confidence: 99%
“…27 Early development during childhood of chronic diseases such as obesity, type 2 diabetes, hypertension and coronary heart disease differs between populations, 28,29 and several studies have shown that SES strongly influences the risk of such diseases. 25,30 Health inequalities are most prominent during childhood, 31 and SES inequalities may influence risk of cardiovascular diseases and health. 32,33 In addition, data published indicate that SES differences in adolescent health influence diet quality and both dietary and physical activity patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies to date have controlled for the effect of obesity on the social gradient of risk of type 2 diabetes [9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in British women aged 60-79 y did not Obesity and life course socioeconomic conditions in the elderly E Regidor et al find an association between abdominal obesity and socioeconomic circumstances in childhood, but did find an inverse gradient with socioeconomic circumstances in adulthood . In addition, socioeconomic circumstances in childhood and adulthood showed an inverse association with waist size in adult women in a British study based on the Whitehall II cohort born between 1930 and 1953 (Brunner et al, 1997(Brunner et al, , 1999. In men, no association was observed with childhood socioeconomic circumstances, and the association with adult socioeconomic circumstances disappeared after adjusting for conditions in childhood (Brunner et al, 1997).…”
Section: Comparison With Other Studies and Possible Explanationsmentioning
confidence: 95%
“…In addition, socioeconomic circumstances in childhood and adulthood showed an inverse association with waist size in adult women in a British study based on the Whitehall II cohort born between 1930 and 1953 (Brunner et al, 1997(Brunner et al, , 1999. In men, no association was observed with childhood socioeconomic circumstances, and the association with adult socioeconomic circumstances disappeared after adjusting for conditions in childhood (Brunner et al, 1997). In another study made in the adult population in Australia, the prevalence of abdominal obesity also showed an inverse association with socioeconomic circumstances in adulthood in women, but no association in men (Ball et al, 2002).…”
Section: Comparison With Other Studies and Possible Explanationsmentioning
confidence: 99%